APLIKASI KOMPOS MUCUNA BRACHTEATA SEBAGAI UPAYA REKLAMASI LAHAN TERHADAP SIFAT FISIKA DAN KIMIA TANAH PASCA ERUPSI DI KABUPATEN KARO - chaula lutfia saragih; Fauzul Azhimah (Universitas Quality, 2022)
Volcanic ash resulted in the death of many farmers' crops on the slopes of the mountain. The area of land in the agricultural sector damaged by the eruption of Mount Sinabung, North Sumatra reached 50,921 ha, consisting of food crops, horticulture, and plantations and 12,399 ha of which crop failure. Problems that arise in volcanic plant growing land if used as media are not suitable to support plant growth optimally. This research was conducted at the location of soil sampling in Sukadebi Village, Namateren District, Karo Regency. This study aims to reclaim the post-eruption soil by utilizing organic material from Mucuna Brachteata compost so that it can be reused into productive agricultural land through sustainable environmental conservation. This research was conducted in 2021, using an experimental method with data analysis of Randomized Block Design. The results showed that the post-eruption soil and mucuna brachteata compost and the interaction of the two treatments had a significant effect on the parameters of the physical properties of the soil, but did not significantly affect the parameters of the chemical properties. Based on the results of the study, it is recommended to conduct further research by giving higher doses to the treatment of mucuna brachteata compost.